STEM IN BIOLOGY CLASSROOM: EXPLORING IMPLEMENTATION CHALLENGES IN INDONESIAN SCHOOLS - Rahmadayanti, Annesha; Rahmayanti, Rita; Aswin, Pani (Universitas Negeri Medan, 2025)
STEM-based learning (Science, Technology, Engineering, and Mathematics) has the potential to enhance the relevance of biology education to 21st-century life through interdisciplinary and project-based approaches. However, its implementation in Indonesia still faces various challenges. This review article aims to identify the key barriers to implementing STEM in biology education, particularly concerning teacher readiness, facilities and infrastructure, and educational policy support. This study employed a narrative literature review method based on 15 national and international journal articles published between 2015 and 2025. Sources were collected through Google Scholar, DOAJ, ScienceDirect, and SpringerLink using the keywords “STEM education,” “biology learning,” and “Indonesia.” The review found four major challenges: (1) limited teacher competence in designing interdisciplinary learning; (2) lack of laboratory and technological facilities; (3) misalignment between the curriculum and assessment systems with STEM principles; and (4) low student motivation and literacy in STEM. Several initiatives, such as teacher training, project-based learning practices, and the integration of local contexts, have shown promising results. This study highlights the need for comprehensive strategies to strengthen teacher capacity, provide adequate infrastructure, and align educational policies to ensure that STEM implementation in biology education can be more effective and sustainable in the Indonesian context.